(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: To determine anti-biofilm effect of fresh garlic extract (FGE) on Staphylococcus aureus biofilm production and the relationship between methicillin resistance and biofilm production intensity. Methods: Clinical S. aureus isolates were identified methicillin resistant S. aureus (MRSA) by cefoxitin disc diffusion method. The anti-biofilm effects of FGE on S. aureus biofilm biomass determination was done using crystal violet assay. Results: Among 71 S. aureus isolates, MRSA were 37 (52.1%). Among biofilm producers, comparison of biofilm biomass (absorbance at 492 nm) showed no significant differences in biofilm formation ability between MRSA and MSSA (p=0.325). Use of 10% FGE decreased biofilm production in MRSA and MSSA by 40.4% (p<0.001) and 48.1% (p<0.001) respectively. Detachment assay using sodium dodecyl sulfate showed that control group biofilm biomass was decreased by 41.2%, while test group was decreased by 61.7% (p<0.001). Conclusion: Garlic extracts has potency as an anti-biofilm agent and could be developed and used to manage different S. aureus biofilm related infections.